Acceptability of depot medroxyprogesterone in women attending general outpatient department: A cross sectional study - Chaudhuri, Sonai; Rai, B. K.; Giri, R; Yadav, A; Giri, S (Health Renaissance, 2017)
Background: Depomedroxy progesterone (DMPA) is most commonly used contraception among the Nepalese women of reproductive age group. Objective: To study the perceived positive and negative aspects regarding the use of DMPA amongst women presenting to the General Outpatient Department of BPKIHS, Dharan, Nepal. Method: This is a cross sectional descriptive study which is conducted at the general out patient department (GOPD) of the B.P. Koirala Institite of Health Science, Dharan, Nepal for a period of one year where a questionnaire was distributed among 100 female patients and their responses were collected. Result: Most widely used contraceptive method was Depot Medroxy progesterone (69%). The most sought after reason for continued use, was "easy to follow dose" (30%) whereas "difficulty with compliance with other contraception" (26%) remains the next important reason. "Privacy (16%) helped the patients to continue the usage whereas “Easily/only available contraception (5%) made rest of the participants to continue the use of Depot medroxyprogesterone. Conclusion: Depot Medroxy Progesterone Acetate is a highly effective, convenient to use non daily hormonal contraception which is widely accepted in Nepalese women when used after proper counseling by clinicians or other health professionals. Health Renaissance 2015;13(2): 7-13